Relasi Dialektis Agama, Masyarakat, Dan Media - Elis, Elis (KOMUNIKA, 2020)
AbstractReligion as an important element in human life gives shape and direction to human thought patterns, feelings and actions. Religion balances the orientation of values, forms of hope and the ideal ego of humans. Religious and social life experiences rapid development along with revolutionary changes in the media. At the stage of modernization, the development of media is already an industry with a variety of cultures that complement it. The relation between religion and the media as an inseparable entity in religious studies is an important study to do, by critically analyzing the elements in it, in the form of objective reality and subjective reality. However, dialectical media or the popular term us a double-edge knife. So, in this paper will discuss how dialectical relations betweem religion, society and the media